A socio-technical framework for internet-of-things design - Dong H. Shin; Sungho Kim; Yeonho Hong; Kyungmi Chung; Jaeyeol Jeong (International Telecommunications Society (ITS), 2015)
This study presents a case application of a socio-technical framework to assess and predict the development of the Internet of Things (IoT) in Korea. Applying a socio-technical system approach to the IoT, this paper seeks a clear understanding of how the IoT will evolve and stabilize in a smart environment. It investigates the complex interaction between social and technical aspects of the IoT, by highlighting the co-evolution, interaction, and interface, which constitute the next generation network environment. It describes the challenges in designing, deploying, and sustaining the diverse components of the IoT, and provides a snapshot of Korea's current approach to meeting this challenge. Finally, the findings of this study provide insights into these challenges and opportunities, by offering a socio-technical analysis of IoT development. The insights help to conceptualize how the IoT can be designed and situated within human-centered contexts.
Keywords: 330; Internet of Things; Contextual approach; South Korea; Socio-technical perspective